Influence Of Solution Concentration And Equilibrium Time On Phosphorus Sorption In Calcareous And Non-Calcareous Soils - Joardar, JC; Sikder, S; Hasib, SB (SAARC Journal of Agriculture, 2020)
Low availability of phosphorus (P) due to P sorption onto soil is one of the major hindrances that greatly affect crop production. So, the understanding of P-soil interactions plays a vital role for increasing agronomic efficiency as well as proper P management. For optimal crop production, annual P application rates should be in equilibrium with the rate of P sorption by soil to ensure the presence of sufficient P in soil. So, it is important to identify the rate of P sorption with time. The focus of this study was to determine and compare the influence of solution P concentrations and equilibrium time on P sorption in calcareous and noncalcareous soils. In the experiment, 0, 2.5, 5, 10, 20 and 50 μg P ml-1 solutions were taken and the sorption rate was investigated at 6, 12, 24 and 48 hour time periods. The results indicate that the P retention onto soil significantly increased with increasing concentration of solution P. Equilibrium time also influenced P sorption. The maximum P sorption was found after 24 hours. After 48 hours, some desorption of fixed P was observed that reflects the reversibility of sorbed P with time. The higher P sorption was found in calcareous soil than in noncalcareous soil irrespective of equilibrium time and solution P concentration. SAARC J. Agri., 17(2): 117-126 (2019)